2021
DOI: 10.31578/job.v10i2.190
|View full text |Cite
|
Sign up to set email alerts
|

Debt Service Payments and Economic Growth in Nigeria

Abstract: The problems of accumulating capital for the provision of basic infrastructures in the less developed countries (LDCs), Nigeria in particular, have been the challenges deterring their consistent growth. This is also compounded by the accumulation of debt service payment areas which constitute one of the serious obstacles to the inflow of external resources into the economy. From the foregoing, there is need to examine the impact of debt service payments on economic growth in Nigeria. The study made use of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is crucial to look at the measures taken to address Nigeria's debt issues in the 1980s (Chidubem, 2023) One of these measures is the federal government's embargo on new loans and its orders to state governments to reduce their external borrowing; debt service payments are also kept to a minimum by putting a portion of export money aside to promote domestic growth (OECD, 2017). Among other measures taken are Debt restructuring as well as the formation of the debt management office by the presidency (Adegboyega, 2021). Little wonder it was asserted categorically that all debts should be project-tied (Vincent et al, 2021).…”
Section: Nigerian Debt Management Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to look at the measures taken to address Nigeria's debt issues in the 1980s (Chidubem, 2023) One of these measures is the federal government's embargo on new loans and its orders to state governments to reduce their external borrowing; debt service payments are also kept to a minimum by putting a portion of export money aside to promote domestic growth (OECD, 2017). Among other measures taken are Debt restructuring as well as the formation of the debt management office by the presidency (Adegboyega, 2021). Little wonder it was asserted categorically that all debts should be project-tied (Vincent et al, 2021).…”
Section: Nigerian Debt Management Issuesmentioning
confidence: 99%
“…Bonds 185,026,886 ,879.94 96,527,951,065 .07 348,980,936,94 1.20 630,535,774,886.21 FGN Savings Bond 116,995,150 .45 123,326,177.23 100,101,637.18 340,422,964 188,364,772 ,069.17 103,883,183,87 6.20 376,437,754,16 7.61 668,685,710, 112.98 Source: DMO Website 39,969.19 16,617,190 Source: DMO Website Figure 3 gives an estimate of the total public debt portfolio of Nigeria and shows a significant amount of debt still outstanding. It is noticeable that Nigeria's external debt stock significantly affects her economic growth was made to evaluate the impact of debt on a few key macroeconomic indicators in the Nigerian economy (Adegboyega, 2021). It also showed that Nigeria's gross fixed capital formation and debt service payments had a big relationship.…”
Section: Nigerian Debt Management Issuesmentioning
confidence: 99%